Remote Audit Quality: Factors and Determinants - Novita Nugraheni; Sila Ninin Wisnantiasri (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
a. (1) The Covid-19 pandemic, occurring during the digital revolution era, significantly impacted the auditing profession. The work-from-home (WFH) model is advantageous as it allows employees greater flexibility, mitigates traffic congestion—particularly for those in metropolitan areas—and decreases transportation expenses. Conducting a remote audit may provide significant challenges, particularly in performing physical examinations in the field. Organizations that have performed remote audits have employed many technologies to sufficiently fulfill the requirement for physical field inspections; (2) This study aims to answer the above problems, namely by explaining remote audits with several factors that can influence the quality of remote audits.; (3) This study employs a quantitative methodology utilizing primary data collected via questionnaires. This study comprises independent and dependent variables. The participants in this study were auditors from Jakarta and Medan.; (4) Results: Summarize the article's main findings; and (5) The impact of information technology, Audit Evidence, going concern, integrity on the quality of remote audits is demonstrably positive and significant, but There is no evidence to demonstrate that professional skepticism influences the quality of remote audits.